Lean-logistics in constructive geography: theoretical and methodological foundations - Udovychenko, Viktoriia; Udovychenko, Iryna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Research problem introduction. The main research goal of this paper is to provide the lean-logistics geosystem research concept as a contemporary approach of constructive geography closely connected with industry as a part of the service sector based on leading scientific principles, GIS-technologies and remote sensing data processing software involvement, and to give some details about this concept applied implementation. All these arguments allow us to specify and to study in-depth the peculiarities, key types, and specificities of the lean-logistics. In this paper, Lean-logistics is understood as an environmental service that helps to improve biodiversity and a stable environment. Lean-logistics itself can be developed as a type of modelling land use and land management activities. This activity can be even thought of as educational innovation with nature-based solutions. The key geographic-centered ideas of the concept of Lean-logistics are integration, engineering, economization, ecologization, socialization, and humanization of modern human activities. The methodological basis of Lean-logistics is presented by three sections, such as Section I. Theory of logistics (for instance, such aspects as general characteristics of logistics and its key features, Varieties of logistics and its classification, Lean logistics as a science: its place in logistics, key distinct features, etc.), Section II. Applied logistics (with such aspects as Military logistics, Business logistics, Environmental logistics, Urban logistics, and Logistics services), and Section III. Logistical construction (Lean-construction of commodity flows and Lean-construction in the field of services). The practical basis of Lean-logistics is formed by logic modelling (studios). Logic modelling in Lean-logistics are called logistics studios and are understood as a form of active practical activities of researchers. Summarizing and generalizing key ideas discussed in the text, the authors underline that the conceptual framework of the lean-logistics geosystem research is based on the implementation of four cross-cutting lines such as environmental security and sustainable development, health and safety, civic responsibility, business undertaking, and financial literacy. All of them aimed at forming a conscious citizen, all areas of activity of which are permeated by logistics chains. Concluding the research, the authors emphasize that the lean-logistics concept may be quite useful within the proposed content of Lean-logistics as a page navigator E-collection in the form of a book trailer. Some pages of it contain examples of the multimedia scrapbook of interactive exercises (deal with some definite sections and/or topics) which are presented using the Print Screen-visualization of the logistics lotto. The use of such tools, forms, technologies, techniques in the study of the content of “Lean-logistics in geography”, as E-collection, book-trailer, hotlist, multimedia scrapbook, mind mapping software, QR-coding, Print Screen-visualization, with active use of GIS, educational Internet services, modernizes the learning process and with systematic use in practice makes them necessary and appropriate in the knowledge about geography and constructive geography.